ANALISIS YURIDIS ATAS KLAIM HAK MILIK ATAS TANAH OLEH INSTANSI PEMERINTAH - Sudiro Basana; Muhammad Yamin; Syafruddin Kalo; Faisal Akbar Nasution (Ilmu Hukum Prima (IHP), 2023)
We are researching to learn how the government controls land ownership according to the Basic Agrarian Law and what happens when they claim ownership of land. We also want to know how they use the term "Property Rights" and what legal things could happen because of that. This study used the Normative Juridical method, which means using legal sources to find the truth based on the logic of law. One way to gather information is by reading books and articles. The research found that the Basic Agrarian Law gives people the right to control and use land in different ways, like owning property, farming, renting buildings, etc. The government ensures that people use land fairly and take care of it. They also decide who can have land and ensure the rules are followed. If there are problems with land, they can help solve them. They also keep track of who owns the land.